2021
DOI: 10.21203/rs.3.rs-608014/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insight Into Impacts of Sewage Discharge and River Self-Purification on Microbial Dynamics and Pathogenicity in River Ecosystem

Abstract: Sewage directly discharge causes serious environmental problems. Here, the effects of treated and untreated sewage on the river ecosystem were investigated. The variations of microbial community structure, including infectious pathogenic bacteria and functional bacteria related to nitrogen, phosphorus, and COD metabolism were studied in detail. Bacterial diversity and richness were significantly decreased, while, Proteobacteria containing various infectious pathogens, such as Vibrio and Helicobacter, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…At the genus level, we found that prometryn significantly increased the abundance of Zoogloea and a Firmicutes bacterium ZOR0006 but decreased the abundance of Shewanella in all exposure groups. Zoogloea has been reported to have multifunctional metabolic capabilities, including effects such as influencing the secretion of extracellular polymeric substances (EPS) [78]. The Firmicutes bacterium ZOR0006 belongs to the family Erysipelotrichaceae and is thought to be associated with metabolic disorders and inflammatory diseases in the host [79,80], which were indeed found to be significantly associated with hepatopancreatic immunity and inflammation in Pearson correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, we found that prometryn significantly increased the abundance of Zoogloea and a Firmicutes bacterium ZOR0006 but decreased the abundance of Shewanella in all exposure groups. Zoogloea has been reported to have multifunctional metabolic capabilities, including effects such as influencing the secretion of extracellular polymeric substances (EPS) [78]. The Firmicutes bacterium ZOR0006 belongs to the family Erysipelotrichaceae and is thought to be associated with metabolic disorders and inflammatory diseases in the host [79,80], which were indeed found to be significantly associated with hepatopancreatic immunity and inflammation in Pearson correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Industrialization has resulted in a significant deterioration in the integrity of the water resources as a result of unmanaged wastewater disposal from industrial operations such as mining, pharmaceuticals, and textile (Ali et al 2017;Xie et al 2022). Industrial activities contribute a range of inorganic and organic contaminants to water systems, altering the water quality upon which biological life relies (Azzam and Tawfik 2015).…”
Section: Industrial Wastewatermentioning
confidence: 99%
“…Sewage sludge or biosolids are organic and inorganic compounds produced by the biological activity of microbes in wastewater treatment plants Xie et al 2022). The production of biosolids has grown in recent decades as a result of the use of aerobic methods in sewage treatment, such as the activated sludge process (Abdul et al 2022b;Tawfik et al 2022a).…”
Section: Introductionmentioning
confidence: 99%